AI and the future of banking - Boobier, Tony, 1956- (Wiley finance editions, 2020)
"AI and the Future of Banking is an informative guide on the applications of Cognitive Analytics/Artificial Intelligence (AI) to the banking industry. The book will equip any industry participant, including new entrants to the industry, with the essential information to understand the implications of data and analytics on their roles, responsibilities and personal career development, with focus on the use of analytics to create operational effectiveness, customer retention and finance and risk management. While a combination of theory and published case studies, it will not be a technical book (i.e. about IT architecture, platforms and algorithms) or a detailed review of a specific working area but rather an easy read for those with limited or no IT background. The book will also discuss the concept of data-driven 'Open Banking, ' which is a process that uses 'APIs' to share information securely, without having to reveal passwords. IDC say that by 2020, 50% of all businesses will be using cognitive analytics, which are intelligent and self-learning systems that respond to human voices rather than needing to be 'coded'. The use of Cognitive Analytics/Artificial Intelligence (AI) Systems and data in banking is set to accelerate. The cognitive or a 'AI' computing market is estimated to exceed $12.0 Billion by 2022, with banking identified as an 'early-mover' industry. Gartner say that AI will be mainstream for banking in 5-10 years. There is already evidence that early-mover banks are beginning to investigate these new technologies. However, there are many laggards and market maturity is inconsistent, with knowledge transfer being critical at this stage"--